Comparative study of different response spectra based on isolated structures. Issue 1 (September 2020) - Liu, Lijun; Zhang, Wenfang
Abstract: In order to study the influence of different design response spectra on the internal force of the isolated structure, the response spectra of the "Code for Seismic Design of Buildings" (Abbreviated as SD), the response spectra of "Design Standards for Seismic Isolation of Buildings" (draft for comments)(Abbreviated as ID) and the response spectra based on pseudo acceleration calibration(Abbreviated as PA) are analyzed. Compared with SD response spectra, ID response spectra adopts the (1/T) attenuation mode in the long period, which reduces the value of the earthquake influence coefficient in the long period of the response spectrum. At the same time, there is no overshoot phenomenon in ID response spectra. This paper presents the response spectrum basic on structural elastic displacement. PA response spectra considers the influence of different sites on the long-period structure, and adds the characteristic period corresponding to different sites. The calculation shows that compared with the calculation result of SD response spectra, the floor shear force calculated by ID is reduced, and the reduction ratio is between 31% and 36%. Compared with the floor shear force obtained by using PA response spectra, the reduction ratio is between 19% and 29%.